مداواة الأمراض في ظلال القرآن الكريم: دراسة موضوعية تحليليّة: THE CURE OF DISEASE IN THE SHADOWS OF THE NOBLE QUR’ĀN: A THEMATIC ANALYSIS STUDY - Bey Zekkoub, Abdelali (Maʿālim al-Qurʾān wa al-Sunnah, 2022)
Allāh has revealed a comprehensive religion, which covers all aspects of life for humanity, and adequate for them for all ages. Therefore, Allāh has created to every disease a suitable remedy, which tackles it. However, the unawareness of the cures of maladies in the Qur’ān has led to the negligence of the implementation of these rules in coping with such diseases. Further, the Contemporary medicine has had the lion's share in dealing with the maladies, which resulted in a defective cure. Therefore, this study aims to shed light on how to cure the maladies from a Qurʾānic perspective. Besides, it will pave the path to eradicate all diseases, which can contaminate the body, the soul as well for a sole individual and the entire society. By employing the inductive and deductive method, the study concluded that natural medicine, Qurʾānic medicine, and prophetic medicine, especially the recitation of Sūrat al-Fātiḥah, al-Baqarah, Āl ʻImrān, al-Kahf, al-Isrāʼ, al-Mulk, al-kāfirīn, al-Ikhlāṣ, al-Falaq, al-Nās, Āyat al-Kursī, ends of Sūrat al-Baqarah, al Ruqyah al-Sharʻīyah, seeking of refuge, and the authentic prophetic supplications; guard the muslim against all kinds of harm, with the permission of God Almighty, except death and old age, but not as necessary, so whoever was afflicted by illness while maintaining these various medicines, that is the decree of God Almighty, and he has great wisdom in his command and destiny.